Multilateral development banks and private sector financing: The case of IFC - George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
The paper examines the role of the multinational development banks in private sector financing with a particular focus on the International Finance Corporation (IFC). The aim of the paper is to bring to focus, in an analytical manner, the past activities and operations as well as the problems and prospects of the Corporation. Simple econometric analysis is also being carried out to test a number of hypotheses regarding IFC finance such as whether IFC finance is an addition to or a substitution for private capital flows as well as the relationship between IFC finance and growth in IFC finance-recipient countries and regions. The central conclusion of the paper is that the Corporation plays a rather significant role in development financing in many developing countries, although its role as a catalyst in private sector financing needs to be reexamined in view of the mixed findings reported in the paper. Granger-causality tests seem to suggest that there is no clear evidence regarding its role as a catalyst in the area of private sector financing. The results are mixed and region specific, thus leaving little room for generalization. Finally, the paper discusses areas where in the case of IFC reforms are most needed, particularly in the light of recommendations included in the Meltzer Report. – IFC ; private sector financing ; multinational development banks ; causality tests
Keywords: F33; O19; 330; Entwicklungsbank